Molybdenum Rhenium (MoRe®) as a Biologically Superior Alloy for Foot and Ankle Implants. Issue 3 (14th September 2018) - Pedowitz, David; Parekh, Selene; Adams, Samuel; Nunley, James; Easley, Mark; Hyer, Christopher; Brigido, Stephen
Category: Other Introduction/Purpose: The most common complications in orthopaedic surgery of the foot and ankle documented in the literature are postoperative infections with a frequency between 1 and 8%. The development of an implant-associated infection can be a potentially devastating complication following foot and ankle surgery. This leads to a high number of revision surgeries after initial fracture stabilization and potential loss of function of the joint and quality of life in the long-term follow-up. Titanium, the most commonly used alloy for foot and ankle implants, has limited strength and is notch-sensitive so repetitive stress leads to fatigue failure of implants and limits design options. Better materials with both optimized mechanical and biological properties could result in the development of superior foot and ankle implants. Methods: Several studies were performed to evaluate the biological properties of MoRe®: A study was conducted to characterize the hydrophilic properties by contact angle comparisons of the MoRe alloy compared to Titanium. A cell growth study was conducted to look at the influence of MoRe alloy on osteoblast growth and differentiation as compared to Titanium. A bone implantation study was conducted based on ISO 10993: Biological Evaluation of Medical Devices, Part 6: Tests for Local Effects after Implantation to evaluate the local tissue and bone response of MoRe® alloy test coupon compared to Titanium controls, when implanted in the mid-shaft femoral bone of rabbits for 4, 13 and 26 weeks. Biofilm formation study was conducted to quantify attachment and biofilm development of S. aureus bacteria upon MoRe® alloy in comparison to CoCr alloy in a well-controlled, reproducible, ex vivo laboratory experiment. Results: MoRe®, composed purely (99.99%) of molybdenum and rhenium, is a cofactor to the enzymes xanthine and sulfite oxidase, which are essential to bone metabolism. Rhenium is an inert metal with no biological affect. MoRe® has superior hydrophilicity (CA 37°±3°) compared to Titanium (CA 58°±3°), a key factor in cell adhesion, migration and replication. Pre-osteoblast cell seeding was found to be equivalent between MoRe° and Titanium alloy (10, 000 cells/cm2). The bone implantation study demonstrated continued bone maturation over time for both MoRe® and Titanium implant sites with similar osteoconduction and bone remodeling histology of the cortical and medullary bone at 4, 13 and 26 weeks. The biofilm study found that S. aureus better colonized cobalt chrome alloy in comparison to MoRe® (p = 0.009). Conclusion: The MoRe® alloy, with its advantageous biological properties and hydrophilicity, offers great promise for the design of a new generation of bio-friendly foot and ankle implants with superior cell growth, osseointegration and biofilm resistance resulting in better outcomes for patients.